Hambatan Penerapan Table Official pada Popda Cabang Bolabasket Kabupaten Purbalingga - Ridlo Al Cholik; Aris Mulyono (Universitas Negeri Semarang, 2023)
The purpose of this study was to find out the obstacles to the implementation of the Official Table at the Purbalingga district basketball branch. This research is a qualitative descriptive study using a narrative design with data collection techniques through observation, interviews and documentation. The subjects of this research are table officials or table officers and several match officials who are on duty and play a role in the Popda Basketball Branch event, Purbalingga Regency. Data analysis used data reduction, data display and conclusion drawing/verification. The results of this study indicate that there are several obstacles that occur in the desk clerk. The availability of tools provided by the committee is still inadequate, there are some tools that look very outdated and do not function as they are used. There are some tools that have not been included in the FIBA ​​standard, namely Shot clock. Table officials are selected based on the criteria that they already have experience and understand the match rules and understand the symbols of the referee, even though they do not yet have the legality/official license from PERBASI. Environmental conditions during matches such as spectators and weather also affect the equipment used by table officials. The availability of tools provided by the committee is still inadequate, there are some tools that look very outdated and do not function as they are used.